OP0103 Decreased Lupus Severity in Mir155 Deficient Mice. (10th June 2014) - Leiss, H.; Salzberger, W.; Gessl, I.; Kozakowski, N.; Blüml, S.; Puchner, A.; Niederreiter, B.; Steiner, G.; Smolen, J.; Stummvoll, G.
Abstract : Background: MicroRNAs (miRs) recently came into view as an important class of regulators of gene expression that are associated with a variety of biological functions. Deregulation of endogenous miR155 was observed in many autoimmune conditions, including systemic lupus erythematosus (SLE). Objectives: We herein examine the role of miR155 in the development of systemic manifestations in murine pristane induced lupus (PIL) by evaluating the severity of organ involvement and assessing serum antibody-levels and T helper cell homeostasis. Methods: MiR155-deficient (miR155-PIL group) and C57/Bl6 (WT-PIL group) mice were injected i.p. with 0.5ml of pristane or PBS as control (WT-PBS group). PIL is an induced model of SLE where typical auto-abs profile and organ involvement develop over a considerable time period ranging from 6 to 10 months. In order to observe the effects of miR155 deficiency in fully developed SLE, we analyzed the mice 8 months after induction. Animals were monitored for clinical signs of glomerulonephritis (GN) by using urine assay strips. In order to analyze and compare disease severity, a blinded specialist appraised histological features of GN using the composite kidney biopsy score (KBS), as described before. Histological features of pneumonitis were quantified by an image analysis system (Osteomeasure®): Lungs were scored for the severity of perivascular inflammation by analyzing the numbers of affected vessels and the area of the inflammatory infiltrate. In order to assess the composition of these infiltrates, specimens were stained with B220 (B), CD3 (T), Neu7/4 (neutrophils) and F4/80 (macrophages) and analyzed by cell-identification algorithms for nuclear segmentation (HistoQuest®). Lymphocytes were isolated from spleens and analyzed separately for each mouse by standard FACS procedures. For analysis of the Th1, 2 or 17 subsets, respectively, cells were re-stimulated in vivo with anti-CD3 and anti-CD28abs. Results: Lungs were affected in both pristane-treated groups (WT-PIL and miR155-PIL), but not in controls. MiR155 deficient mice (miR155-PIL) had reduced lupus severity as indicated by significantly decreased perivascular inflammatory area with B cells being the most prominent inflammatory cell type in the HistoQuest analysis (Fig. 1A ). Without showing clinical abnormalities WT-PIL had a more severe renal involvement in the kidney biopsy score than miR-PIL (Fig. 1B ). Corresponding with reduced severity in organ involvement, miR155-PIL had lower serum levels of anti-dsDNA-abs (Fig. 1C ), decreased frequencies of CD4 + cells (14.24±0.7587 vs. 18.04±1.075, p=0.01) and slightly lower frequencies of activated CD4 + CD25 + Foxp3 – cells (1.539±0.1279 vs. 1.838±0.2259, p=ns.). Interestingly, also frequencies of CD4 + CD25 + Foxp3 + regulatory T cells were lower in Mir155-PIL (1.689±0.1388 vs. 2.375±0.2320, p=0.03). Upon restimulation, CD4 + cells showed a more pronounced Th2 and Th17 response in WT-PIL, but no significant differences in Th1 phenotype (Fig. 1D ). Conclusions: MiR155 deficiency in PIL mice did not prevent the development of disease, but was associated with less severe lung and kidney involvement, lower serum auto-abs levels and lower Th17 and Th2 frequencies when analyzed in fully established PIL after 8 months. Thus, antagonisation of miR155 might be a beneficial future approach in treating SLE. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5340